Correlation and benefits of portfolio diversification among equity markets of developed countries and emerging countries in South East Asia region - Haron, Razali; Zainal Abidin, Sazali (Faculty of Economics and Management, Universiti Putra Malaysia, 2006)
The specific objective of this paper is to generate and analyze the average correction coefficient of return, between the Malaysian equity market and equity markets in other selected countries during 17 year period from January 1987 to December 2003. The period of 17 years is further divided into 13 different sub-periods divided by pre, during and post crisis to study the differences in pattern of average correlation coefficients during the sub-periods. The study found that average correlations were higher during the non-crisis periods as compared to crisis periods. The study also divided the group of countries according to region (South East Asia), developed countries and emerging countries. It is found that the Malaysian market is more correlated with the regional market and emerging markets as compared to the developed markets. The study also analyses the evolution of correlation of the Malaysian market and other countries throughout the study period. It concludes that there is a weak or no linear relationship on correlations between the Malaysian market and foreign markets and the time factor. This suggests that there is instability in market correlations over time. In the perspective of Malaysian investors, this paper concludes that international portfolio diversification still offers diversification benefits.